A Successful Vancomycin-Resistant Enterococci Reduction Bundle at a Singapore Hospital. (21st October 2015) - Fisher, Dale; Pang, Long; Salmon, Sharon; Lin, Raymond T.P.; Teo, Cathrine; Tambyah, Paul; Jureen, Roland; Cook, Alex R.; Otter, Jonathan A.
Abstract: We report a reduction in the vancomycin-resistant enterococci (VRE) rate from a peak of 1.5 cases per 1, 000 admissions (95% confidence interval [CI], 1.0−2.1) in August 2012 to 0.5 per 1, 000 admissions (95% CI: 0.3−1.0) by January 2015, associated with a bundle of interventions. Infect. Control Hosp. Epidemiol. 2015;37(1):107–109